Complete chloroplast genome sequence of Salix sinopurpurea (Salicaceae) - Feiyi Guo; Kangjia Liu; Yachao Wang; Enze Li; Zhenfeng Zhan; Zhixiang Zhang (Mitochondrial DNA. Part B. Resources, 2021)
Salix sinopurpurea is a morphologically special shrubby willow characterizing opposite leaves. Here, we reported the complete chloroplast (cp) genome sequence of Salix sinopurpurea. The cp genome is 155,546 bp in length, including a large single-copy (LSC) region of 84,412 bp, a small single-copy (SSC) region of 16,216 bp, and a pair of inverted repeated regions of 27,459 bp. The cp genome of Salix sinopurpurea encodes 130 genes, including 85 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Phylogenetic tree showed that Salix sinopurpurea is closely related to Salix psammophila and Salix suchowensis.